2019
DOI: 10.1111/inm.12645
|View full text |Cite
|
Sign up to set email alerts
|

The validity and utility of violence risk assessment tools to predict patient violence in acute care settings: An integrative literature review

Abstract: To examine risk assessment tools to predict patient violence in acute care settings. An integrative review of the literature. Five electronic databases – CINAHL Plus, MEDLINE, OVID, PsycINFO, and Web of Science were searched between 2000 and 2018. The reference list of articles was also inspected manually. The PICOS framework was used to refine the inclusion and exclusion of the literature, and the PRISMA statement guided the search strategy to systematically present findings. Forty‐one studies were retained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 76 publications
0
29
0
1
Order By: Relevance
“…In the past decade, several violence risk‐assessment instruments have been developed, validated, and deployed to screen high‐risk patients (Ghosh et al . 2019). Additionally, training programmes were undertaken to strengthen nurses’ techniques and skills for violence prevention and control (Bromley & Painter 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several violence risk‐assessment instruments have been developed, validated, and deployed to screen high‐risk patients (Ghosh et al . 2019). Additionally, training programmes were undertaken to strengthen nurses’ techniques and skills for violence prevention and control (Bromley & Painter 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Die aktuelle S3-Leitlinie "Verhinderung von Zwang: Prävention und Therapie aggressiven Verhaltens bei Erwachsenen" empfiehlt außerdem den Einsatz von Vorhersageinstrumenten für aggressives Verhalten wie der "Broset Violence Checklist" [36,37] oder der "Dynamic Appraisal of Situational Aggression" [38,39] in der klinischen Routinediagnostik [40]. Daneben existiert noch eine Reihe weiterer Checklisten und Fragebögen, um das Gewaltpotenzial von Patienten mit psychischen Erkrankungen einzuschätzen [41]. Feindseligkeit lässt sich symptomatisch auch aus der Erhebung der "Positive and Negative Syndrom Scale" -PANSS [42] oder mit dem Hostilitätssyndrom nach dem AMPD [43] strukturell gut erfassen und als Zielsymptomatik für therapeutische Interventionen benennen.…”
Section: Prävention Fremdaggressiven Verhaltens In Stationären Psychiunclassified
“…A recent review article in the International Journal of Mental Health Nursing addressed the validity and utility of risk assessment tools for violence in acute care settings (Ghosh et al, 2019). Five electronic databases were searched between 2000 and 2018, and of 379 records identified, 41 studies met the inclusion criteria, and 16 risk assessment tools were identified.…”
mentioning
confidence: 99%
“…The V‐RISK‐10 has been investigated and presented in three publications on predictive validity for violence risk assessment among patients admitted to acute psychiatric wards. However, two V‐RISK‐10 studies (Eriksen et al ., 2016 and Hartvig et al , 2011) were presented as Ps33 studies by Ghosh et al (Table 1, Ghosh et al, 2019). In the discussion section of the review, they mention that the Ps33 had been reduced to 10 items and given a new name, the V‐RISK‐10.…”
mentioning
confidence: 99%
See 1 more Smart Citation